The Social Milieu of the Church and Religious Coping Responses: A Longitudinal Investigation of Older Whites and Older Blacks - Krause, Neal (2010)
The purpose of this study is to see if the social environment of the church influences the use of religious coping responses over time. The following theoretical relationships were embedded in the conceptual model that was developed to evaluate this issue: (1) people who go to church more often are more likely to feel their congregation is highly cohesive (e.g., share the same values and beliefs); (2) individuals who worship in highly cohesive congregations are more likely to receive spiritual support (i.e., encouragement to adopt religious teachings and principles) from their fellow church members; (3) people who receive more spiritual support will be more likely to adopt religious coping responses. In the process of evaluating this model, tests were performed to examine the influence of racial culture. Data from a nationwide longitudinal survey of older adults provide support for each link in the conceptual model. Pervasive racial cultural differences were also found: Older blacks were more likely to be deeply involved in each facet of religion than older whites.